Effects of Hydrochlorothiazide on Tenofovir Disoproxil Fumarate-Induced Nephrotoxicity in Rats - G.Al-Rakhat, Iman; N.Al-Shawi, Nada (Iraqi Journal of Pharmaceutical Sciences, 2019)
Tenofovir disoproxil fumarate, a nucleotide reverse transcriptase inhibitor utilized for the treatment of hepatitis B virus and human immunodeficiency virus infections; and is now one of the most widely used antiretroviral drug. However, tenofovir disoproxil fumarate can induce nephrotoxicity, which may be attributed to the interaction between such drug and the organic anion transporters (hOAT1, and OAT3) with consequent changes in levels of some parameters that may have a role in nephrotoxicity. Thiazide diuretics have high to intermediate potency of inhibition of OAT1s and OAT3; thus, it may possess nephroprotective effects. This study was designed to investigate whether hydrochlorthiazide has nephroprotective effects on tenofovir disoproxil fumarate-induced nephrotoxicity in rats. Twenty eight healthy adult male albino rats weighing 180-200g were utilized in this study for duration of 5weeks (35 days) treatment. Rats were randomly divided into four groups (7animals each). Group I: Negative control (orally given distilled water) by gavage tube; Group II: Rats orally received 600 mg/kg/day tenofovir disoproxil fumarate by gavage tube; Group III: Rats orally administered hydrochlorothiazide alone at a dose (10 mg/kg/day) by gavage tube, and Group IV: Rats orally administered hydrochlorothiazide at a dose (10 mg/kg/day) plus tenofovir disoproxil fumarate 600 mg/kg/day by gavage tube. On day 36 of the study, after euthanization of each animal by diethyl ether, 3-5ml of blood samples were collected from each rat by an intra-cardiac puncture, then centrifuged at 3000 rpm for 15 minutes to obtain serum, which was then transferred into suitable plain tubes and preserved at -20 °C; and it was utilized for the estimation of cystatin C and IL-10 level. Rats administered tenofovir disoproxil fumarate for 5 weeks (group II) produced a significant -elevation (P<0.05) in serum cystatin C level and –reduction in serum IL-10 levels compared to negative control group (group I); similarly, administration of hydrochlorothiazide alone to rats (group III) produced a significant -elevation (P<0.05) in serum cystatin C level and –reduction in serum IL-10 levels compared to negative control group (group I); also, rats administered combination of hydrochlorothiazide plus tenofovir disoproxil fumarate to rats for 5 weeks (group IV) produced significant elevation (P<0.05) in serum level of cystatin C, and a significant reduction (P<0.05) in IL-10 serum level in treated rats compared to the corresponding levels of negative control animals (group I); beside that in (group IV) rats there were significant reduction (P<0.05) in serum level of both cystatin C, and IL-10 in treated rats compared to the corresponding levels compared to TDF-treated (group II). In conclusion, treatment with hydrochlorthiazide plus tenofovir disoproxil fumarate in an attempt to prevent nephrotoxicity induced by tenofovir disoproxil fumarate is not attained.